The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/md.0000000000026521
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of gestational diabetes mellitus in patients with polycystic ovary syndrome

Abstract: The influencing factors of gestational diabetes mellitus (GDM) in the polycystic ovary syndrome (PCOS) patients remain unclear, we aimed to investigate the risk factors of GDM in patients with PCOS, to provide reliable evidence for the prevention and treatment of GDM in PCOS patients.PCOS patients treated in our hospital from January 1, 2019 to October 31, 2020 were included. The personal and clinical treatment details of GDM and no GDM patients were analyzed. Logistic regressions were performed to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
1
20
0
1
Order By: Relevance
“…The results still show that GDM did not increase the incidence of PE in pregnant women with PCOS, regardless of whether GDM occurred early or later ( 153 ). Another prospective study in China found that the incidence of PE in PCOS pregnant women with GDM is significantly higher than that in pregnant women without GDM but did not analyze whether it was independent associated with PE ( 154 ). Thus, the effect of GDM on PE in pregnant women with PCOS is less than the effect of PCOS on PE in women with GDM.…”
Section: Effect Of Gdm On the Occurrence Of Pe In Twin Pregnancy And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results still show that GDM did not increase the incidence of PE in pregnant women with PCOS, regardless of whether GDM occurred early or later ( 153 ). Another prospective study in China found that the incidence of PE in PCOS pregnant women with GDM is significantly higher than that in pregnant women without GDM but did not analyze whether it was independent associated with PE ( 154 ). Thus, the effect of GDM on PE in pregnant women with PCOS is less than the effect of PCOS on PE in women with GDM.…”
Section: Effect Of Gdm On the Occurrence Of Pe In Twin Pregnancy And ...mentioning
confidence: 99%
“…A Chinese prospective study found no difference in the incidence of PE between women with GDM with PCOS and those without PCOS, although the result was affected by factors such as small sample size and early intervention (151). Pregnant women with PCOS combined with GDM tend to be older and have higher pre pregnancy BMI (152)(153)(154). It is necessary to determine whether GDM associated with PE in pregnant women with PCOS.…”
Section: Pcosmentioning
confidence: 99%
“…Many risk factors for the development of GDM are similar to those for T2DM. These risk factors include overweight and obesity, excessive gestational weight gain, advanced maternal age, multiparity, family history of T2DM or GDM, polycystic ovary syndrome (PCOS), physical inactivity, GDM in the previous pregnancy, certain ethnicities (including Asian ethnicity), a previous macrosomic child, Westernized diet, genetic polymorphisms, and intrauterine environment (low or high birth weight) [48,[59][60][61][62][63][64][65].…”
Section: Defective Beta-cell Adaptation During Pregnancy and Gestatio...mentioning
confidence: 99%
“…Li et al [31 ▪▪ ] conducted a retrospective study of pregnant individuals with PCOS in China ( N = 196) using Rotterdam criteria for PCOS and IADPSG criteria for GDM to evaluate possible GDM risk factors. Using logistic regression models, the authors found several independent risk factors for GDM among pregnant individuals with PCOS: age at least 30 years, BMI at least 24 kg/m 2 , increased insulin resistance [measured by homeostatic model assessment for insulin resistance (HOMA-IR)], elevated testosterone, elevated androstenedione, and low SHBG [31 ▪▪ ]. Increased insulin resistance (HOMA-IR) in individuals with PCOS was proposed as the mechanism predisposing these individuals to GDM during pregnancy [31 ▪▪ ].…”
Section: Risk Factors For Gestational Diabetes In Polycystic Ovarian ...mentioning
confidence: 99%